Haemoglobin Hope: A Rare Hb Variant Causing Spuriously Elevated HbA1c Values on HPLC Assay - Mrinal Gupta; Priyanka Datta; Pragna Rao (National Journal of Laboratory Medicine, 2016)
Introduction: Hb Hope is a clinically asymptomatic βchain variant [beta136 (H14) Gly→Asp (GGT→GAT)]. It is more prevalent in Mediterranean region of the world than in Asian countries and extremely rare in India. Aim: To evaluate the interference of clinically silent and extremely rare variant; haemoglobin Hope (Hb Hope) on the final reported value of glycated haemoglobin (HbA1c) by high performance liquid chromatography (HPLC). Materials and Methods: Eight EDTA blood samples showed very high values of HbA1c (>50 gm%) when processed by Bio-Rad Variant II turbo (HPLC). These were further processed for by capillary electrophoresis to look for the abnormal haemoglobin. Glycated Hb was also measured by immunoturbidimetry. Results: On HPLC, single abnormally high peak was observed for all the samples in the chromatogram leading to very high glycated haemoglobin values while in immunoturbidimetric assay reportable values were obtained. Moreover, capillary electrophoresis showed the presence of haemoglobin Hope in all the samples. Conclusion: Hb hope might lead to overestimation and possible misinterpretation of glycated haemoglobin results. Hb Hope is extremely rare in India but the possibility of interference by such clinically silent variant should always be kept in mind while interpreting the HbA1c values.